Bridging gaps in groundwater: a woman leader led multistakeholder platform experience from Nepal - KC, Sumitra; Khadka, Manohara (2025)
The presentation titled "Bridging Gaps in Groundwater: A Woman Leader-Led Multistakeholder Platform in Barahathawa Municipality, Nepal" by Ms. Sumitra KC and Dr. Manohara Khadka highlights the challenges and solutions related to groundwater governance in Barahatthawa Municipality, Nepal. Groundwater is vital for agri-food system transformation, but its governance is complex due to the three-tiered federal structure in Nepal. There is a gap in evidence and knowledge on sustainable extraction thresholds and equitable access. We presented our action research on strengthening groundwater governance using multi-stakeholder platform as a solution for coordinated planning for managing and using groundwater sustainably and equitably.